Circular RNA: a novel biomarker for progressive laryngeal cancer - Xuan, Lijia (Am J Transl Res, 2016)
Circular RNAs (circRNAs), a class of endogenous RNAs, are characterized by covalently closed continuous loop without 5’ to 3’ polarity and polyadenylated tail. Recent studies indicated that circRNAs might play an important role in cancer. However, the function of circRNA in laryngeal squamous cell cancer tissues (LSCC) is still unknown. In this study, we investigated the expression of circRNAs in 4 paired LSCC tissues and adjacent non-tumor tissues by microarray analysis. Results showed significant upregulation (n = 302) of or downregulation (n = 396) of 698 circRNAs in LSCC tissues. We further detected hsa_circRNA_100855 as the most upregulated circRNA and hsa_circRNA_104912 as the most downregulated circRNA using qRT-PCR methods. Results showed that hsa_circRNA_100855 level was significantly higher in LSCC than in the corresponding adjacent non-neoplastic tissues. Patients with T3-4 stage, neck nodal metastasis or advanced clinical stage had higher hsa_circRNA_100855 expression. The hsa_circRNA_104912 level was significantly lower in LSCC than in corresponding adjacent non-neoplastic tissues. Patients with T3-4 stage, neck nodal metastasis, poor differentiation or advanced clinical stage had a lower hsa_circRNA_104912 expression. Overall, our data suggest that circRNAs play an important role in the tumorigenesis of LSCC and may serve as novel and stable biomarkers for the diagnosis and progress of LSCC.